CD52 is a molecular target in advanced systemic mastocytosis. Issue 8 (23rd April 2014) - Hoermann, Gregor; Blatt, Katharina; Greiner, Georg; Putz, Eva Maria; Berger, Angelika; Herrmann, Harald; Cerny‐Reiterer, Sabine; Gleixner, Karoline V.; Walz, Christoph; Hoetzenecker, Konrad; Müllauer, Leonhard; Reiter, Andreas; et al.
Abstract : Advanced systemic mastocytosis (SM) is an aggressive hematopoietic neoplasm with poor prognosis and short survival times. So far, no curative therapy is available for affected patients. We have identified the cell surface antigen CD52 (CAMPATH‐1) as a molecular target expressed abundantly on the surface of primary neoplastic mast cells (MCs) in patients with advanced SM. In contrast, neoplastic MCs of patients with indolent SM and normal MCs expressed only low levels or did not express CD52. To study the mechanisms of CD52 expression and the value of this antigen as a potential therapeutic target, we generated a human MC cell line, designated MCPV‐1, by lentiviral immortalization of cord blood‐derived MC progenitor cells. Functional studies revealed that activated RAS profoundly promotes surface expression of CD52. The CD52‐targeting antibody alemtuzumab induced cell death in CD52 + primary neoplastic MCs obtained from patients with SM as well as in MCPV‐1 cells. NSG mice xenotransplanted with MCPV‐1 cells survived significantly longer after treatment with alemtuzumab (median survival: 31 d untreated vs. 46 d treated; P =0.0012). We conclude that CD52 is a novel marker and potential therapeutic target in neoplastic MCs in patients with advanced SM.—Hoermann, G., Blatt, K., Greiner, G., Putz, E. M., Berger, A., Herrmann, H., Cerny‐Reiterer, S., Gleixner, K. V., Walz, C., Hoetzenecker, K., Müllauer, L., Reiter, A., Sotlar, K., Sexl, V., Valent, P., Mayerhofer, M. CD52 is a molecular target in advanced systemic mastocytosis. FASEB J. 28, 3540–3551 (2014). www.fasebj.org